2006
DOI: 10.1016/j.jalgebra.2005.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Dual canonical bases for the quantum general linear supergroup

Abstract: Dual canonical bases of the quantum general linear supergroup are constructed which are invariant under the multiplication of the quantum Berezinian. By setting the quantum Berezinian to identity, we obtain dual canonical bases of the quantum special linear supergroup O q (SL m|n ). We apply the dual canonical bases to study invariant subalgebras of the quantum supergroups under left and right translations. In the case n = 1, it is shown that each invariant subalgebra is spanned by a part of the dual canonical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…A brief review of early works on the theory and applications of quantum supergroups can be found in [63]. Partially successful constructions of crystal and canonical bases for quantum supergroups were given in [1,12,37,53,55,54,72,73].…”
Section: Introductionmentioning
confidence: 99%
“…The present paper continues the investigation started in [2]. We shall construct the canonical basis of the tensor powers of the natural representation of U q (gl m|n ) by relating them to the Kazhdan-Lusztig theory [7] for Hecke algebras of type A.…”
Section: Introductionmentioning
confidence: 77%
“…In a recent publication [2] , we began a study of the canonical basis and dual canonical basis of quantum supergroups and their function algebras. Recall that crystal bases and canonical bases for ordinary quantum groups and the associated quantized function algebras were introduced by Kashiwara [3,4] and Lusztig [5] in the early 1990s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have not included them in the text in Chapter 5, since they are very technical and could disrupt the exposition. We invite the reader to consult [53,110,163] for more details and the proofs of our statements, that cannot be included here.…”
Section: Quantum Supergroupsmentioning
confidence: 99%